Cloud Application Development Methodology - Benfenatki, Hind; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P. (Proc. of the IEEE/WIC/ACM International Conference on Web Intelligence (WI 2014), 2014)
Nowadays, cloud applications are developed in Platforms as a Service following the PaaS architecture imposed by several providers. We find in the literature some works describing frameworks and architectures for cloud software development, but there is a lack of a generic methodology which covers the whole application development lifecycle. Our work fits into the perspective of defining a generic methodology for automatic cloud-based services-oriented business application development. We focus on the requirements expression phase by defining a ”requirements vocabulary”, which is based on Linked USDL principles. The methodology we propose is designed for non-technical users. The highlight of this work is that it uses cloud computing and SOA advantages to allow a business stakeholder to proceed to business application development simply by defining his/her business requirements in terms of business functionalities; QoS parameters; and user preferences.